Ammonia adsorptive capture and Sequential Phosphorus Recovery as two nutrient products from anaerobic membrane bioreactor (AnMBR) swine permeate - Mckee-Rist, Nicholas (My University, 2025)
Managing swine wastewater presents environmental challenges and resource recovery opportunities within a circular economy framework. Phosphorus is an essential nutrient for agricultural productivity, yet its primary source, phosphate rock, is a finite resource. Swine wastewater, a byproduct of concentrated animal feeding operations (CAFOs), contains high concentrations of phosphorus (P) and nitrogen (N), which contribute to eutrophication and greenhouse gas emissions if not adequately managed. This study explores the potential for nutrient recovery from swine wastewater using a combination of physicochemical processes to sequester phosphorus and ammonia in reusable forms. Specifically, anaerobic treatment systems, including Anaerobic Membrane Bioreactors (AnMBRs), were employed to facilitate microbial fermentation and selective nutrient capture, with a focus on optimizing the production of recoverable phosphorus precipitates and ammonia-based fertilizers. The sequential recovery process involved pH adjustment to 4.5 using hydrochloric acid (HCl) to strip bicarbonate ions, followed by the addition of calcium oxide (CaO) and magnesium chloride (MgCl₂) to precipitate phosphorus. Two chemical addition sequences were tested: CaO followed by MgCl₂ and MgCl₂ followed by CaO. The CaO-first sequence at a 0.5:1 Ca:P molar ratio, followed by MgCl₂ at a 1:1 Mg:P ratio, demonstrated the highest phosphorus removal efficiency (89.60% after 7 hours) and favored the formation of amorphous calcium phosphate (ACP), a highly soluble quick-release fertilizer. Struvite formation was also observed at lower Ca ratios, indicating the potential for producing mixed fertilizers with varying nutrient release rates. Controlled pH conditions (7-9) were critical for enhancing phosphorus precipitation, while high alkalinity led to unwanted calcium carbonate (CaCO₃) formation, reducing the fertilizer value of the product. In addition to phosphorus recovery, ammonia capture on clinoptilolite was evaluated as a precursor to liquid fertilizer production, with adsorption capacities influenced by influent concentration and contact time. The findings highlight the importance of optimizing chemical addition sequences, reaction times, and pH conditions to maximize nutrient recovery and produce high-quality fertilizer products. This research provides a framework for integrating phosphorus and nitrogen recovery into agricultural and municipal wastewater treatment systems, reducing reliance on mined phosphate, and promoting sustainable nutrient management. By recovering valuable nutrients from swine wastewater, this study contributes to the development of circular nutrient use, enhancing fertilizer production from waste streams, and mitigating the environmental risks associated with nutrient-laden agricultural runoff. The integration of these technologies underscores the potential for decentralized wastewater treatment systems to contribute to sustainable agriculture and environmental stewardship
Keywords: Nutrient Recovery from treated swine permeate